Modulating the Surface Ligand Orientation for Stabilized Anionic Redox in Li‐Rich Oxide Cathodes. Issue 13 (3rd March 2021) - Liu, Yanchen; Zhu, He; Zhu, Hekang; Ren, Yang; Zhu, Yizhou; Huang, Yalan; Dai, Liang; Dou, Shuming; Xu, Jie; Sun, Cheng‐Jun; Wang, Xun‐Li; Deng, Yida; et al.
Abstract: Anionic redox chemistry is emerging as a key concept in the development of high‐energy lithium‐ion batteries, as it enables a nearly doubled charge storage capacity, aiding the development of high‐capacity batteries. However, the anionic reactivity is frequently irreversible from charge to discharge, leading to rapid decay of the capacity and voltage of batteries over long‐term cycling. Although the possibility of controlling the anionic redox reactions by tuning the geometric and electronic structures has recently been proposed, the implementation of this strategy is still a critical challenge. Herein, a strategy is proposed to improve the anionic redox reversibility of a model anionic redox active cathode material, Li1.2 Ni0.13 Co0.13 Mn0.54 O2, by tuning the surface ligand geometry via the growth of a lattice‐compatible spinel LiCoO2 coating layer on the particle surface. Detailed local structure and first principles investigations reveal that the shape and orientation of the octahedral layer in the host lattice are modified. Accordingly, a two‐band oxygen redox behavior is triggered in the ligand‐orientation‐regulated Li‐rich cathode, leading to enhanced reversibility, and thus, remarkably improved capacity and voltage retention over cycling. This study highlights the importance of controllable ligand orientation, carving a new path for the development and design of Li‐rich cathodes in the future. Abstract : A novel ligand‐orientation‐regulated (LOR) Li‐rich cathode is put forward to improve the anionic‐redox reversibility of Li1.2 Ni0.13 Co0.13 Mn0.54 O2, implemented by coating a lattice‐compatible spinel LiCoO2 onto the surface of particles. Accordingly, a two‐band oxygen‐redox behavior is triggered in the LOR cathode, enabling remarkably improved capacity and voltage retention over cycling.